Investigating Fear of Missing Out: A comparative study of gender, employment status, and social media accounts - Hafni, Merri; Sianturi, Bona (Universitas Negeri Padang, 2022)
The purpose of this study was to describe the condition of fear of missing out (FoMO), and to investigate differences in FoMO based on gender, employment status, and number of social media accounts. This study uses a quantitative approach to the type of comparative research. Sampling using incidental sampling technique, the sample in this study amounted to 469 respondents (male = 112; female = 357). Data were collected using the FoMO instrument. Data were analyzed using anova with the help of JASP software. The results showed that FoMO conditions were experienced by all respondents, but FoMO in respondents who did not work or students were more worried about not having access to their smart phones. This is of course related to the number of social media accounts and free time (respondents who do not work or students have a lot of free time) to access the internet, because smart phones cannot work optimally when there is no internet access. Another finding is that female students who have two to three social media accounts and even those who have more than three are more dominant in responding to the FoMO instrument compared to male. However, when viewed from the average, men who do not work to experience the highest FoMO condition compared to men who have jobs, even with women who work and those who do not work.